Phytochemical Standardization of Semicarpus Anacardium and Evaluation of Anti-haemorrhoidal Activity in Animal Model - Kajal Kumari; Ashish Mishra; Shilpi Mishra (Asian Journal of Pharmaceutical Research and Development, 2025)
Many herbal remedies individually or in combination have been recommended in various medical treatments for the cure of different diseases. Semecarpus anacardium (SA) Linn (Family: Anacardium), is a plant well known for its medicinal value in ayurvedic and siddha system of medicine. The Semecarpus anacardium nuts are used for various medicinal and pharmacological purposes from ancient period. It is well proved that hemorrhoids are pathological conditions. In these conditions there occurs vasodilation at recto anal portion at severe level. This promotes the inflammation of surrounding tissues, further leading to secondary difficulties. These are extravasation of fluid into interstitial space that is due to increased vascular permeability and migration of large quantity of inflammatory cells (granulocytes and monocytes). In the present investigation, croton oil has been used as inducer/phlogistic agent to induce experimental hemorrhoids. Croton oil causes severe inflammation due to the release of inflammatory lipid metabolites likes (prostaglandins, leukotrienes, lipoxins) cytokines (TNF- α and IL-6). These factors, alone or in combination, regulate the activation of resident cells (fibroblasts, endothelial cells, macrophages and mast cells).